Environmental and cultural-based macromedia flash learning media as a reading solution for the alpha generation - Alwi, Nur Azmi; Anita, Yesi; Kenedi, Ary Kiswanto; Irwandi, Irwandi; Akmal, Atika Ulya (International Journal of Innovative Research and Scientific Studies, 2025)
This study addresses the low early reading ability among Alpha generation children, attributed to the lack of suitable media aligned with their technological environment. It aims to examine the effectiveness of Macromedia Flash-based learning media rooted in local environment and culture in enhancing reading skills. A quasi-experimental method with a nonequivalent control group design was applied, involving 200 children aged 7–9 years. Data were collected using an observation checklist and analyzed using SPSS through normality, homogeneity, paired sample t-tests, and independent t-tests. The findings revealed a significant improvement in children's reading skills after using the culturally and environmentally contextualized Macromedia Flash media. The average improvement reached 68%, indicating the media’s effectiveness in fostering reading development. The study concludes that integrating familiar cultural and environmental elements into digital learning tools can enhance engagement and outcomes for Alpha generation learners. These results offer practical guidance for educators seeking innovative, context-relevant methods to improve literacy among young children.